2021
DOI: 10.1111/cts.13172
|View full text |Cite
|
Sign up to set email alerts
|

Adapting regulatory drug‐drug interaction guidance to design clinical pharmacokinetic natural product‐drug interaction studies: A NaPDI Center recommended approach

Abstract: Pharmacokinetic drug interactions precipitated by botanical and other natural products (NPs) remain critically understudied. Investigating these complex interactions is fraught with difficulties due to the methodologic and technical challenges associated with the inherently complex chemistries and product variability of NPs. This knowledge gap is perpetuated by a continuing absence of a harmonized framework regarding the design of clinical pharmacokinetic studies of NPs and NP-drug interactions. Accordingly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…As mentioned earlier, clinical kratom-drug interaction studies are warranted for targets identified in this review, particularly CYP2D6, CYP3A, and P-gp. Studies should be conducted using well characterized kratom products and relevant probe drugs as described elsewhere for evaluating potential pharmacokinetic natural product-drug interactions ( Kellogg et al, 2019 ; Cox et al, 2022 ). Evaluation of a well characterized kratom product representative of the majority of marketed products, administered in a form mimicking typical usage, will ensure generalizability of the results.…”
Section: Perspectives and Path Forwardmentioning
confidence: 99%
“…As mentioned earlier, clinical kratom-drug interaction studies are warranted for targets identified in this review, particularly CYP2D6, CYP3A, and P-gp. Studies should be conducted using well characterized kratom products and relevant probe drugs as described elsewhere for evaluating potential pharmacokinetic natural product-drug interactions ( Kellogg et al, 2019 ; Cox et al, 2022 ). Evaluation of a well characterized kratom product representative of the majority of marketed products, administered in a form mimicking typical usage, will ensure generalizability of the results.…”
Section: Perspectives and Path Forwardmentioning
confidence: 99%